Challenges and Efforts of School Stakeholders in Enhancing P5 through the Theme “Bangunlah Jiwa Raganya” at SMP Negeri 31 Batam - Sondari, Resti; Rianto, Slamet; Febriani, Trina (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is based on the implementation of the Pancasila Student Profile Strengthening Project (P5) as part of Indonesia’s curriculum shift from the 2013 Curriculum to the Merdeka Curriculum. The research aims to identify: (1) the challenges faced by school stakeholders in enhancing P5 through the theme